Theoretical Study of Plasma Using Different Dimension of Hollow Cathode - Mishra, L. N.; Khanal, K. (Journal of Nepal Physical Society, 2019)
This article deals about the theoretical study on DC hollow cathode glow discharge using different hollow cathode geometry. The mechanism of discharge is analyzed at various gas pressure and radial configuration. The dependence of temperature on gas pressure has been elucidated with the help of Scotty limit. Discharge behavior with radius has also been explained. It is revealed that floating potential increases as gas pressure increases whereas plasma potential decreases as gas pressure increases. This theoretical work resembles with the experimentally measured results. This work might be useful for the plasma processing for industrial purposes.